Evaluasi Kinerja Pelayanan Terpadu Satu Pintu pada dinas Penanaman Modal dan Pelayanan Perizinan di Kabupaten Dairi - Sitorus, Hetty Malina; Warjio, Warjio; Isnaini, Isnaini (Universitas Medan Area, 2020)
This study aims to evaluate the performance of the One-Stop Integrated Investment and Licensing Services Office of Dairi Regency as PTSP organizer. Service Performance can be seen from the dimensions of Productivity, Service Quality, Responsiveness, Responsibility and Accountability. Researchers sought to explore information on the influencing factors that affect organizational performance, namely the dimensions of organizational support, management ability and competence of the apparatus. The study was conducted using a descriptive method with a qualitative approach that is describing the facts obtained through observation, in-depth interviews and document review. The conclusion of the research shows that the performance of Dairi Regency DPMPPTSP in general is still not optimal, but on the dimensions of responsiveness and accountability have shown better results. Management capacity and organizational support are inadequate, while the competence of the apparatus is quite good. Commitment of regional heads together with their staff is needed to improve service facilities and infrastructure, especially the construction of vehicle parking facilities at the DPMPPTSP Office of Dairi Regency, to improve the regional investment climate, as well as the incentive policy for apparatus proportionally.